1996
DOI: 10.5144/0256-4947.1996.269
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Obesity Among Saudi Males in the Riyadh Region

Abstract: Attendees of 15 health centers in Urban and rural areas in the Riyadh region were screened for obesity during May and June 1994. Systemic selection yielded 1580 Saudi males for analysis. The mean age was 33.6 ± 13.5 years and body mass index (BMI) was 26.9 ± 5.7 kg/m 2 . Only 36.6% of subjects were their ideal weight (BMI < 25 kg/m 2 ), while 34.8% were overweight (BMI 25-29.9 kg/m 2 ), 26.9% were moderately obese (BMI 3.0-40 kg/m 2 ) and 1.7% were morbidly obese (BMI > 40 kg/m 2 ). Middle age, lower education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 17 publications
(13 reference statements)
4
24
1
Order By: Relevance
“…Though obesity is reported to be more frequent among the illiterates or those with a low level of education in Saudi Arabia, 18,19 the present study supports earlier findings 3 that it remains a substantial health problem even among those with higher level of education. To add further to this grim situation, it has been observed that, in general, a large proportion of those who need to lose weight lack motivation.…”
Section: Discussionsupporting
confidence: 81%
“…Though obesity is reported to be more frequent among the illiterates or those with a low level of education in Saudi Arabia, 18,19 the present study supports earlier findings 3 that it remains a substantial health problem even among those with higher level of education. To add further to this grim situation, it has been observed that, in general, a large proportion of those who need to lose weight lack motivation.…”
Section: Discussionsupporting
confidence: 81%
“…Obesity is currently an escalating epidemic that affects many countries in the world including the Arabian Gulf region (Al Isa, 1995;Al Shammari et al, 1994;Al Mahroos and Al-Roomi, 1999: El Mugamer et al, 1995: AlAwadi and Amine, 1989, where this condition is responsible for increasing death rates annually. It is a major contributor to precipitating or aggravating chronic diseases (Guo and Chumlea, 1999), including type 2 diabetes mellitus, coronary heart disease, and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although inborn errors of metabolism are a major pediatric public health problem in the Kingdom, no such study has been previously conducted on this disease.…”
mentioning
confidence: 99%